Non-alcoholic fatty liver disease in obese persons with diabetes - Tomašević Ratko; Golubović Gradimir; Stanković Dragana; Gluvić Zoran; Dugalić Predrag; Pavlović Aleksandar (Vojnosanitetski Pregled)
Background. Obesity, diabetes and different lipid metabolic disorders are the most frequent risk factors for nonalcoholic fatty liver disease, presented with a high variability in clinical and histological findings. Case report. We presented a case of 37-year-old male, suffering from type 2 diabetes mellitus, grade III obesity (BMI 45 kg/m2) and multiple metabolic disorders. Abdominal ultrasound revealed hepatomegaly during the last six months. Laboratory diagnostics showed increased serum transaminase levels. Serologic markers for viral hepatitis B and C were negative. The patient denied significant alcohol consumption. Liver biopsy and pathohistologic finding revealed macro- (III grade) and microvesicular (I grade) fatty degeneration, as well as mixed-cell portal infiltration with moderate liver fibrosis, corresponding to the typical presentation of NASH (Non Alcoholic Steatohepatitis). Conclusion. NASH treatment options include the reduction of body mass and an adequate antidiabetic and dislipidemia treatment. The aim of all therapeutic measures was to stop the progression of the disease, to prevent the progression of fibrosis and the development of of cirrhosis. .